2020
DOI: 10.1002/sctm.18-0283
|View full text |Cite
|
Sign up to set email alerts
|

Cystic renal-epithelial derived induced pluripotent stem cells from polycystic kidney disease patients

Abstract: Autosomal‐dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease, leading to kidney failure in most patients. In approximately 85% of cases, the disease is caused by mutations in PKD1. How dysregulation of PKD1 leads to cyst formation on a molecular level is unknown. Induced pluripotent stem cells (iPSCs) are a powerful tool for in vitro modeling of genetic disorders. Here, we established ADPKD patient‐specific iPSCs to study the function of PKD1 in kidney development and cyst f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Similarly, Huang et al have differentiated functional kidney-like cells (KLCs) from iPSCs of patients with ADPKD carrying a deletion of the SAMSN1 gene, demonstrating that this mutation might influence KLCs’ differentiation capacity and/or functionality in water transportation and albumin absorption 67. Moreover, iPSCs have been successfully produced from patients with PKD to investigate the influence of PC1 on ciliary PC2 expression,68 from patients with ADPKD to study the role of PKD1 in kidney development and cyst formation69 and from patients with BBS mutated in the BBS10 gene, to highlight the role of cilia genes in the correct production of neural crest cells, an important feature to elucidate in patients with BBS with neural crest-derived facial defects 70. Finally, a number of studies have exploited iPSC-derived retinal cells to dissect the retinal defects associated with some primary ciliopathies.…”
Section: Modelling Primary Ciliopathies: From Animal Models To Patien...mentioning
confidence: 99%
“…Similarly, Huang et al have differentiated functional kidney-like cells (KLCs) from iPSCs of patients with ADPKD carrying a deletion of the SAMSN1 gene, demonstrating that this mutation might influence KLCs’ differentiation capacity and/or functionality in water transportation and albumin absorption 67. Moreover, iPSCs have been successfully produced from patients with PKD to investigate the influence of PC1 on ciliary PC2 expression,68 from patients with ADPKD to study the role of PKD1 in kidney development and cyst formation69 and from patients with BBS mutated in the BBS10 gene, to highlight the role of cilia genes in the correct production of neural crest cells, an important feature to elucidate in patients with BBS with neural crest-derived facial defects 70. Finally, a number of studies have exploited iPSC-derived retinal cells to dissect the retinal defects associated with some primary ciliopathies.…”
Section: Modelling Primary Ciliopathies: From Animal Models To Patien...mentioning
confidence: 99%
“…The latter is advantageous because the procedure is non-invasive. Furthermore, since the epigenetic memory of donor cells influences iPSC differentiation, the use of (urine-derived) renal cells appears favorable for the creation of kidney organoids [65,66].…”
Section: Sources Of Pluripotent Stem Cellsmentioning
confidence: 99%
“…To fill this knowledge gap, researchers led by Joost H. Gribnau (Erasmus Medical Center Rotterdam, Oncode Institute, Rotterdam, The Netherlands) generated ADPKD patient‐specific iPSCs from human cystic renal epithelial cells derived from primary renal tubular epithelial cell cultures to evaluate the function of PKD1 in kidney development and cyst formation. Reporting in a recent STEM CELLS Translational Medicine article, 5 Kenter et al reported the maintenance of heterozygous germline mutations in PKD1 after detailed mutational analysis in ADPKD‐iPSCs; however, they failed to detect any “second‐hit” mutations in other ADPKD‐related genes possibly involved in disease pathogenesis. Indeed, the authors found evidence that the reprogramming process itself induced many of the additional mutations detected.…”
Section: Related Articlesmentioning
confidence: 99%
“…In the first of our Featured Articles published this month in STEM CELLS , Cieslar‐Pobuda et al report a novel link between the DNMT3B DNA methyltransferase, metabolic flux, and the self‐renewal and differentiation of human embryonic stem cells (ESCs) 4 . In a Related Article published recently in STEM CELLS Translational Medicine , Kenter et al generated and characterized human induced pluripotent stem cells (iPSCs) from cystic and healthy control renal epithelial cells for the in vitro modeling of kidney development and cystogenesis, and highlighted the existence of a kidney‐specific DNA methylation‐based epigenetic memory of origin 5 …”
mentioning
confidence: 99%